Analisis penerapan layanan Sapa Pustakawan di Perpustakaan IAIN Kudus - Radiya Wira Buwana (Perpustakaan Universitas Gadjah Mada, 2021)
Introduction. IAIN Kudus Library has a plan to implement Sapa Pustakawan service as part of an information retrieval service to support reference services in satisfying users’ the information needs.. This study examines the concept of the service that planned to be applied at IAIN Kudus Library. Data Collection Methods. This paper used a descriptive qualitative approach by using interviews supporting by document studies. Data Analysis. The data from the interviews with the head of the IAIN Kudus Library and librarians of IAIN Kudus Library about the Sapa Pustakawan services were analysed by involving related references and theories to obtain several concepts. Results and Discussions. The results indicate that in order to implement Sapa Pustakawan, the library manager needs to pay attention to some aspects namely place, product, human resources (librarian), and promotion. Conclusion. The study shows that Sapa Pustakawan plays a signifincat role in helping users for reference services including anti-plagiarism by implementing those aformentioned aspects.